2021
DOI: 10.1158/0008-5472.can-20-1954
|View full text |Cite
|
Sign up to set email alerts
|

Fat Induces Glucose Metabolism in Nontransformed Liver Cells and Promotes Liver Tumorigenesis

Abstract: Hepatic fat accumulation is associated with diabetes and hepatocellular carcinoma (HCC). Here we characterize the metabolic response that high fat availability elicits in livers prior to disease development. After a short term on a high fat diet, otherwise healthy mice showed elevated hepatic glucose uptake and increased glucose contribution to serine and pyruvate carboxylase activity compared to control diet mice. This glucose phenotype occurred independently from transcriptional or proteomic programming, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 55 publications
(66 reference statements)
0
54
0
Order By: Relevance
“…It has been shown that high-fat content in the diet can alter glucose metabolism in normal liver cells to a Warburg-like phenotype, suggesting that excessive fat availability can metabolically prime normal hepatocytes for neoplastic transformation. The hyperactivation of glucose metabolism induced by high-fat availability is mediated by increased peroxisomal ROS production [36], highlighting the close link between energy metabolism and modifications in the oxidative status of the cells. In this sense, the availability of different nutrients and metabolites can influence not only the activity and the expression of anti-and prooxidant enzymes, but also feed metabolic pathways that burst ROS generation, driving metabolic reprograming, and carcinogenesis.…”
Section: Metabolic Dysfunctionmentioning
confidence: 99%
“…It has been shown that high-fat content in the diet can alter glucose metabolism in normal liver cells to a Warburg-like phenotype, suggesting that excessive fat availability can metabolically prime normal hepatocytes for neoplastic transformation. The hyperactivation of glucose metabolism induced by high-fat availability is mediated by increased peroxisomal ROS production [36], highlighting the close link between energy metabolism and modifications in the oxidative status of the cells. In this sense, the availability of different nutrients and metabolites can influence not only the activity and the expression of anti-and prooxidant enzymes, but also feed metabolic pathways that burst ROS generation, driving metabolic reprograming, and carcinogenesis.…”
Section: Metabolic Dysfunctionmentioning
confidence: 99%
“…HFDs profoundly potentiates malignant progress in pancreatic, liver, prostate, colon, and breast cancers [110][111][112][113][114] . Moreover, HFDs synergistically induce the malignant transformation of liver cells or elicit tumorigenesis by nourishing stem cells or suppressing the tumor immune microenvironment [115][116][117] .…”
Section: Lipid Metabolism In Cancer and High-fat Dietsmentioning
confidence: 99%
“…Obesity can modulate glucose metabolism to promote HCC progression. Saturated fatty acids such as palmitate impact cancer stem cell properties, production of reactive oxidative species, and glucose metabolism to enhance HCC initiation and progression ( 24 , 25 ). In addition, feeding a HFD promoted the production of lactate when the mice received glucose ( 25 ).…”
Section: Obesity and Hccmentioning
confidence: 99%
“…Saturated fatty acids such as palmitate impact cancer stem cell properties, production of reactive oxidative species, and glucose metabolism to enhance HCC initiation and progression ( 24 , 25 ). In addition, feeding a HFD promoted the production of lactate when the mice received glucose ( 25 ). T-regulatory cells (Tregs) can proliferate in lactate-rich environments, which mediates suppression effector T cell function ( 26 ).…”
Section: Obesity and Hccmentioning
confidence: 99%
See 1 more Smart Citation